Examining challenges in adopting safety leading indicators for construction projects in South Africa - Adekunle, Samuel; Onatayo, Damilola; Ejohwomu, Isimemen; Aigbavboa, Clinton (Frontiers in Built Environment, 2024)
PurposeThe construction industry has been observed to be one of the most dangerous sectors in which to work; thus, it has struggled to attract new employees and suffered from skill shortages. Another characteristic is adopting a reactive approach to preventing accidents instead of a proactive approach that implements safety-leading indicators. In contributing to achieving a safer construction industry, this study investigated the barriers to achieving a proactive approach to safety in the construction industry.MethodThe study adopted a quantitative approach. Data was collected by randomly administering a well-structured questionnaire to industry professionals in South Africa. One hundred and two questionnaires were collected and used as the basis for data analysis and interpretation by the study.ResultThe analysis of the collected data identified nineteen significant barriers which were clustered into two based on an exploratory factor analysis. The top three ranked significant barriers are Lack of Top management’s commitment to safety, Lack of leadership training and Prioritising productivity over employee safety. The two clusters formed from the nineteen barriers through factor analysis are top management approaches to safety and Safety culture through employee-centric training and accountability.OriginalityConsidering the accident data from South Africa, and the inherent benefits of implementing SLI to overcome this, this study provides critical insights for industry stakeholders and policymakers. It fills a gap that has not been filled in the developing country context before now.